Late entrants into the academic profession: Conceptual constructions of hope in a faculty of Education - Bitzer, EM; Albertyn , RM (South African Journal of Higher Education, 2011)
Professional development of generic black academic staff in South African higher education is viewed against the background of increased emphasis on open dialogue and concern for upward mobility in academe. Open dialogue and liberation create new expectations and challenges for staff. This article describes professional development of academics that embarked on advanced studies in the field of higher education. Using in-depth e-mail conversations with academic staff participating in M.Phil. and Ph.D. programmes, qualitative research was employed to explore developmental experiences. A conceptual framework emerged which reflects the context, process and outcomes of programme participation in formal higher education qualifications. The framework could be the basis for developmental strategies of academic staff – particularly in researchoriented universities with late entrants from a variety of non-traditional backgrounds. Benefits will impact on delivery of quality higher education to the student body and thus contribute to the broader transforming education context in South Africa.